2020
DOI: 10.1016/j.cities.2020.102928
|View full text |Cite
|
Sign up to set email alerts
|

Study of COVID-19 pandemic in London (UK) from urban context

Abstract: COVID-19 transmission in London city was discussed in this work from an urban context. The association between COVID-19 cases and climate indicators in London, UK were analysed statistically employing published data from national health services, UK and Time and Date AS based weather data. The climatic indicators included in the study were the daily averages of maximum and minimum temperatures, humidity, and wind speed. Pearson, Kendall, and Spearman rank correlation tests were selected for data analysis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 64 publications
1
33
1
1
Order By: Relevance
“…Raj, Velraj, & Haghighat (2020) investigated the relationships between virus viability and populating density, climate severity, the volume of indoor spaces and air-conditioning usage in India, through correlation analyses. Traffic volumes on road and travel distance are identified as important factors to explain newly confirmed cases of COVID-19, by Lee et al (2020) who focused on Incheon, South Korea and estimated a linear regression model, and by Ghosh et al (2020) who focused on four UK cities and estimated a mixed-effects model, respectively. Through a bivariate logistic regression model, the household crowding, number of residential units per building, and household structure are found to be associated with COVID-19 transmission in New York ( Emeruwa et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Raj, Velraj, & Haghighat (2020) investigated the relationships between virus viability and populating density, climate severity, the volume of indoor spaces and air-conditioning usage in India, through correlation analyses. Traffic volumes on road and travel distance are identified as important factors to explain newly confirmed cases of COVID-19, by Lee et al (2020) who focused on Incheon, South Korea and estimated a linear regression model, and by Ghosh et al (2020) who focused on four UK cities and estimated a mixed-effects model, respectively. Through a bivariate logistic regression model, the household crowding, number of residential units per building, and household structure are found to be associated with COVID-19 transmission in New York ( Emeruwa et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“… Hamidi et al, 2020 Metropolitan population, activity density (population & employment per square mile), ICU beds per 10,000 population, primary care physicians per 10,000 population Multi-level linear model 1,165 metropolitan counties in the USA Larger metropolitan areas lead to significantly higher COVID-19 infection rates and higher mortality rates Lee et al, 2020 Traffic volumes on roads Single linear regression 6,307 vehicle detection systems (VDS) in South Korea In Incheon there was a positive, but insignificant, linear relationship between the increasing numbers of newly confirmed cases and increasing traffic. Ghosh et al, 2020 Travel distance to London, population density Mixed-effects model Distance from London to four other cities (Birmingham, Leeds, Manchester and Sheffield) As the distance from London increases, the number of COVID-19 cases decreases. Mizumoto & Chowell, 2020 Occupant density on the Diamond Princess cruise ship Mathematical modeling 621epidemiological incidence cases The increased exposure risks associated with high occupant density were demonstrated in the COVID-19 outbreak that occurred on the ship.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The atmospheric factors such as humidity, temperature, or solar irradiation perform inversely to COVID-19 survival. For instance, some recent studies show that COVID-19 transmission is favored by cold and dry weather conditions ( Casanova et al, 2010 ; Ghosh et al, 2020a ). Regarding COVID-19 pandemic transmission, Huang et al (2020) found that the COVID-19 is facilitated in the temperature range from 5 and 15 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The increased speed of global movements, supported by technological progress, provides new opportunities to vira. Pathogens make their way from animals to humans locally in rural areas and spread to more urbanised regions thanks to global networks moving large numbers of people, animals and goods quickly across the globe on a daily basis (United Nations 2020; Ghosh et al 2020). Viewed from this angle, beyond its novelty, COVID-19 does not look exceptional; neither in its ability to spread in space nor in terms of the speed it travels.…”
Section: A Multi-scalar and Multi-systemic Phenomenonmentioning
confidence: 99%